Controle do fluxo de potência em conversores com módulos em ponte completa conectados em cascata para aplicações com baterias de segunda vida - Saccol, Gabriel Avila (2023)
Cascaded H-bridge converters are interesting candidates energy storage systems, since the batteries can be directly connected to the input dc-side of each converter module. However, in second-life batteries energy storage systems, the disparity among the parameters of the batteries require that the modules operate with different power levels. In this case, conventional power balancing methods will lead to an increased distortion on the converter output voltage and high current levels on the semiconductors. Therefore, this Ph.D. Dissertation proposes a generalized single-phase space vector modulation strategy, by selecting the redundant states of a cascaded H-bridge multilevel converter. A closed-loop control method is used to obtain the semiconductors switching states dwell time. The open-delta operating mode is considered to minimize the current demand on the semiconductors in relation to the conventional three-phase deltaconnected converter, for unbalanced power situations. Simulation and experimental results are included to demonstrate the performance of the proposed method.